PERKULIAHAN MEMBACA KRITIS DAN KREATIF MAHASISWA PBSI BERORIENTASI PENDIDIKAN KARAKTER - Denik Wirawati (BAHASTRA, 2015)
Reading skill of Indonesian people was very low included our students. By reading, someone not only got knowledge, but also influenced one’s character. Lecturing Critical and Creative Reading Of Pendidikan Bahasa dan Sastra Indonesia (PBSI) Students Oriented In Character Education To Describe Character education model that integrated in lecturing and giving activity of critical and creatif reading. Reaserch method used qualitative descriptive. This article discussed two cases; (i) character education model that integrated in lecturing critical and creative reading, (ii) giving students’ activity of critical and creative reading. Research result of character education model can be observed by; a. Reading organization, b.Writen purpose, c. How to solve problem, d. Logicallity that be writer in article and, f. Comparing between text and the real fact.